2020
DOI: 10.1111/dth.13799
|View full text |Cite
|
Sign up to set email alerts
|

Cross sectional quality of life assessment in patients with androgenetic alopecia

Abstract: Assessment of quality of life (QOL) of patients with androgenetic alopecia (AGA) has become increasingly important, both in order to evaluate the influence of the disease on patients and the therapy they require. We aimed to assess QOL in subjects complaining from AGA and evaluated the effects of various sociodemographic factors affecting their QOL. QOL was assessed in 400 patients with AGA and 100 controls using the World Health Organization Quality of life (WHOQOL‐BREF) questionnaire. Four domains (physical,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 26 publications
(66 reference statements)
0
32
0
Order By: Relevance
“…Associations between tobacco smoking and the severity of AGA have not been studied intensively. A number of environmental factors were reported to be responsible for the early‐onset and development of AGA 15 …”
Section: Discussionmentioning
confidence: 99%
“…Associations between tobacco smoking and the severity of AGA have not been studied intensively. A number of environmental factors were reported to be responsible for the early‐onset and development of AGA 15 …”
Section: Discussionmentioning
confidence: 99%
“…Regarding the group of skin diseases linked with secondary psychiatric comorbidities, in a study by Elsaie et al 23 about androgenetic alopecia (AGA), the social impact of this dermatosis was significantly higher in patients less than 30 years of age compared to those above 30 years of age. Patients with severer forms of AGA, and longer duration of the condition significantly had higher scores in all domains of QoL, assessed by the World Health Organization Quality of life questionnaire (physical, psychological, social, and environmental) compared to those with less severe forms and shorter duration.…”
Section: Qol In Psychodermatologic Disordersmentioning
confidence: 99%
“…Thus, acne correlated with self-esteem and feelings of shame, as well as stigmatization and subsequent poorer QoL 22. Regarding the group of skin diseases linked with secondary psychiatric comorbidities, in a study by Elsaie et al23 about androgenetic alopecia (AGA), the social impact of this dermatosis was significantly higher in patients less than 30 years of age compared to those above 30 years of age. Patients with severer forms of AGA, and longer duration of the condition significantly had higher scores in all domains of QoL, assessed by the World Health Organization Quality of life questionnaire (physical, psychological, social, and environmental) compared to those with less severe forms and shorter duration.5 | LIAISON CLINICS/INTEGRATED CARE MODELS To assist patients with psychocutaneous disorders, physicians around the world have created novel clinics specifically designed to provide a multidisciplinary care for a comprehensive patient treatment.…”
mentioning
confidence: 99%
“…Therefore, hair loss brings many troubles to people, such as impaired image, impacted self-confidence, failure of a marriage, and love, and may impact people's health. Studies have shown that hair loss can cause various psychological difficulties, such as anxiety, depression, and trauma, and further impair quality of life (QoL) [ 1 3 ]. Androgenetic alopecia (AGA), commonly known as male or female pattern baldness, is the most common progressive hair loss disorder [ 4 ].…”
Section: Introductionmentioning
confidence: 99%